2009
DOI: 10.3727/096504010x12704916124828
|View full text |Cite
|
Sign up to set email alerts
|

The Inhibitor of Growth 1 (ING1) Is Involved in Trichostatin A-Induced Apoptosis and Caspase 3 Signaling in p53-Deficient Glioblastoma Cells

Abstract: Prognosis for patients with glioblastoma multiforme (GBM) is poor. Inhibitors of histone deacetylases (HDACi) like trichostatin A (TSA) are promising alternatives to conventional treatment. Deficient tumor suppressor functions, such as TP53 mutations and p14(ARF)/p16(INK4a) deletions, are characteristic for GBM and can cause resistance to DNA damaging agents such as cisplatin and to HDACi like TSA. The type II tumor suppressor Inhibitor of growth 1 (ING1) is involved in DNA damage response and histone modifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…In this study we have shown that ING1 physically associates with, and is a target substrate of the Src tyrosine kinase in vitro and in vivo , that Src contributes to reducing levels of ING1 by phosphorylation-dependent and phosphorylation-independent mechanisms, and that such reduction blocks the ability of ING1 to induce apoptosis. This suggests that Src may contribute to regulating ING1 levels and thus act to alter cell susceptibility to undergoing apoptosis since ING1 has been reported by many groups to enhance apoptosis [9][11], [41]–[47].…”
Section: Discussionmentioning
confidence: 99%
“…In this study we have shown that ING1 physically associates with, and is a target substrate of the Src tyrosine kinase in vitro and in vivo , that Src contributes to reducing levels of ING1 by phosphorylation-dependent and phosphorylation-independent mechanisms, and that such reduction blocks the ability of ING1 to induce apoptosis. This suggests that Src may contribute to regulating ING1 levels and thus act to alter cell susceptibility to undergoing apoptosis since ING1 has been reported by many groups to enhance apoptosis [9][11], [41]–[47].…”
Section: Discussionmentioning
confidence: 99%
“…ING1 may contribute to trichostatin A-induced apoptosis in p53-deficient glioblastoma cells by regulating the Fas/caspase-3 apoptosis pathway [5]. Furthermore, ING3-mediated UV-induced apoptosis via the Fas/caspase-8 pathway was reported in human melanoma cells [6].…”
Section: Introductionmentioning
confidence: 99%
“…25, 26, 27, 28, 29, 30, 31 Ectopic expression of ING1 also induces apoptosis, 19 and although initial reports suggested this role may be p53-dependent, 20, 32, 33 more recent evidence suggest that the ING family also has effects on apoptosis that are independent of p53. 34, 35, 36, 37 ING1 interacts with proliferating cell nuclear antigen (PCNA) via the PCNA-interacting protein (PIP) domain in a stress-induced manner. 13 The PIP domain is necessary for the ability of ING1 to maximally induce apoptosis upon overexpression and in response to DNA damage.…”
mentioning
confidence: 99%